Ambulatory monitoring of oesophageal pH in reflux oesophagitis using a portable radiotelemetry system. Issue 11 (November 1982) - Branicki, F J; Evans, D F; Ogilvie, A L; Atkinson, M; Hardcastle, J D
Abstract : Gastro-oesophageal reflux has been assessed in 10 symptomatic patients and 10 asymptomatic normal subjects during a study period of 24 hours at work and in the home using a newly developed pH sensitive radiotelemetry capsule and a portable receiving system. Oesophageal pH was continuously monitored by the tethered radiotelemetry capsule and recorded with a portable receiver and a 24-hour cassette recorder, allowing the patient complete freedom of movement so that ambulatory studies could be undertaken during a normal working day. The number and duration of reflux episodes was greater in symptomatic patients than normal subjects during 24-hour studies at home (p less than 0.002). In both groups, reflux occurred more during the day than at night (p less than 0.01). Patients refluxed significantly more at home than when they were in hospital (p less than 0.01). Ambulatory outpatient oesophageal pH monitoring may be useful in the management of patients with atypical symptoms and may demonstrate significant reflux when inpatient investigations and endoscopy findings show minimal abnormality.